2021
DOI: 10.1177/21677026211051324
|View full text |Cite
|
Sign up to set email alerts
|

Rumination Derails Reinforcement Learning With Possible Implications for Ineffective Behavior

Abstract: How does rumination affect reinforcement learning—the ubiquitous process by which people adjust behavior after error to behave more effectively in the future? In a within-subjects design ( N = 49), we tested whether experimentally manipulated rumination disrupts reinforcement learning in a multidimensional learning task previously shown to rely on selective attention. Rumination impaired performance, yet unexpectedly, this impairment could not be attributed to decreased attentional breadth (quantified using a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 120 publications
(168 reference statements)
0
7
0
Order By: Relevance
“…Recent laboratory studies on rumination and reward perception showed that rumination disrupted reinforcement learning (adjusting behavior after error to behavior), thereby impairing learning adaptive behavior and promoting stress-generating behavior; however, participants were not in their perinatal period ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent laboratory studies on rumination and reward perception showed that rumination disrupted reinforcement learning (adjusting behavior after error to behavior), thereby impairing learning adaptive behavior and promoting stress-generating behavior; however, participants were not in their perinatal period ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mothers with their partner's support (n = 374) impairing learning adaptive behavior and promoting stressgenerating behavior; however, participants were not in their perinatal period (44). Rumination might impair concentration and contingency attention associated with adaptive behavior, suggesting that rumination reduces sensitivity to contextual details (45).…”
Section: Variablementioning
confidence: 99%
“…We compared a variety of computational models that might plausibly capture learning and choice processes in the task in terms of HITCHCOCK AND FRANK model comparison (i.e., fit to task data while penalizing for model complexity) and model validation (i.e., ability to capture key features of the data; "Method"). In both experiments, the most successful model (Figure 3) was a Q-learning RL model that learned values of the actions in each state (Q-values) through trial and error, but where the Q-values decayed (Brown et al, 2018;Collins et al, 2014;Hitchcock et al, 2022;Katahira & Toyama, 2021;Niv et al, 2015) over trials toward a default prior via a decay parameter, w,…”
Section: An Rl Computational Model Was Able To Capture Key Task Effectsmentioning
confidence: 99%
“…These changing, state‐based processes are particularly relevant given robust links between affective dysregulation and stress reactivity with EDs (Chami et al, 2019; Lavender et al, 2015; Wonderlich & Lavender, 2017). For instance, in a recent study in individuals with elevated depressive symptoms, researchers used a within‐subjects design to explore the influence of state‐based depressive rumination on reinforcement learning performance, finding that performance was impaired by engagement in rumination (Hitchcock, Forman, et al, 2022). Given the relevance of rumination and other forms of repetitive negative thinking in EDs (Palmieri et al, 2021), this type of manipulation may increase external validity of findings as well as inform more dynamic, context‐dependent models of procedural memory in EDs (Hitchcock, Fried, & Frank, 2022).…”
Section: Back To the Future: Progressing Memory Research In Eating Di...mentioning
confidence: 99%